Kant on Negative Wisdom: Faith and the Counterpurposive in “On the Failure of All Attempted Philosophical Theodicies” - Ferguson, Thomas (Con-Textos Kantianos. International Journal of Philosophy, 2026)
This article rereads Kant’s difficult 1791 essay on theodicy as constructing a challenge to Kant’s own critical system, especially the end of third Critique, in regard to the compatibility of nature and morality and (by extension) of speculative and practical reason. He uses this challenge to redevelop his concept of wisdom, playing down the systematic/teleological role of previous texts and presenting a novel, apophatic mode of wisdom based in sincerity. I argue that authentic theodicy (illustrated in Kant’s reading of Job) “handles” sincerely held doubts by revealing to the faithful moral agent the “inscrutability” of a creation which nevertheless remains wise, and at the same moment disclosing those agents’ own status. Doubts against divine wisdom are not so much answered as contextualized within “good life conduct.” The consequence is a retreat in the farthest ambitions of Kant’s system (the unification of reason), and increased emphasis on self-cognition.